The Pragmatics of Naming in Samuel Richardson’s Clarissa - Christophe LESUEUR (E-REA)
Samuel Richardson’s Clarissa thematizes the name and the associated naming process. Destined to change her name by marrying Solmes, the eponymous heroine uses several borrowed names in her flight. The policies of imposing a name that underlie on the one hand Clarissa’s parents’ endeavors to control the mutation of the signifier, and Lovelace’s on the other, bear witness to the existence of a pragmatics: the name is the subject of quarrels, naming proving to be a vital process. The struggles that purport to assert sway over the name are not only endowed with obvious historical interest in that they allow for a reflection on the perception of processes of mutation of the signifier as important as marriage. They also question the function of naming in the narrative act itself.